EFFECT OF CARIOGENIC FOOD INTAKE ON SALIVARY pH IN CHILDREN (PENGARUH KONSUMSI MAKANAN KARIOGENIK TERHADAP pH SALIVA PADA USIA ANAK) - Henri Hartman; Rhabiah El Fithriyah; Badi Soerachman; Sarah Aulia Rahmah (Journal of Health and Dental Sciences, 2022)
All ages, especially children, favor cariogenic foods. Cariogenic foods are foods that contain fermented carbohydrates, mainly sucrose. Microorganisms are attached to the tooth surface can ferment various types of carbohydrates, becoming acidic and causing a decrease in salivary pH until it reaches a critical point in salivary pH followed by dental caries in the future. Saliva is one of the factors that cause dental caries. This study aimed to determine the effect of cariogenic food intake on changes in children's pH salivary. This research was conducted with a literature study as a reference and analyzed the findings obtained. The sample used was nine pieces of literature consisting of 19 cariogenic foods. This study showed a statistically significant result (p<0.05) in a change of salivary pH value before cariogenic food and after cariogenic food intake. Around 42.53% of children experienced a decrease in salivary pH more significant than the average after cariogenic foods intake, and 57.47% of children experienced a reduction in pH salivary. There are 49.74% of children have pH salivary lower than its average value, which could be lead to demineralization of enamel. DOI : 10.54052/jhds.v1n3.p275-288